Analisis Proses Pembuatan CAM 2SX di PT. XYZ dan PT. ABC - Raihan Fadillah; Viktor Naubnome; Deri Teguh Santoso (Jurnal Serambi Engineering, 2024)
CAM 2SX production process at PT. XYZ and PT. ABC to determine the performance, quality and challenges of these automotive components. The stamping process was found to be effective in producing components at high speed and high precision through various process steps such as stamping, forming, shearing, trimming, punching and quality control (QC). The use of SPCC (Steel Plate Cold Coil) materials, CNC technology and simulation software helps to optimise processes and improve production results. In addition, the importance of qualified and trained human resources is recognised to meet the demands of modern industry, which is realised through the practical work initiative of Singaperbangsa University, Karawang. Strict quality controls are implemented to ensure that each component meets specifications and is free from defects such as scratches, dents, cracks and extrusions. In short, the stamping process is efficient and effective in manufacturing automotive components, but requires attention to detail and strict quality control to achieve optimum results